Adding Dopamine to Proxymetacaine or Oxybuprocaine Solutions Potentiates and Prolongs the Cutaneous Antinociception in Rats. (May 2018) - Chen, Yu-Wen; Chiu, Chong-Chi; Lin, Heng-Teng; Wang, Jhi-Joung; Hung, Ching-Hsia
Abstract : BACKGROUND: We evaluated the interaction of dopamine–proxymetacaine and dopamine– oxybuprocaine antinociception using isobolograms. METHODS: This experiment uses subcutaneous drug (proxymetacaine, oxybuprocaine, and dopamine) injections under the skin of the rat's back, thus simulating infiltration blocks. The dose-related antinociceptive curves of proxymetacaine and oxybuprocaine alone and in combination with dopamine were constructed, and then the antinociceptive interactions between the local anesthetic and dopamine were analyzed using isobolograms. RESULTS: Subcutaneous proxymetacaine, oxybuprocaine, and dopamine produced a sensory block to local skin pinpricks in a dose-dependent fashion. The rank order of potency was proxymetacaine (0.57 [0.52–0.63] μmol/kg) > oxybuprocaine (1.05 [0.96–1.15] μmol/kg) > dopamine (165 [154–177] μmol/kg; P < .01 for each comparison) based on the 50% effective dose values. On the equianesthetic basis (25% effective dose, 50% effective dose, and 75% effective dose), the nociceptive block duration of proxymetacaine or oxybuprocaine was shorter than that of dopamine ( P < .01). Oxybuprocaine or proxymetacaine coinjected with dopamine elicited a synergistic antinociceptive effect and extended the duration of action. CONCLUSIONS: Oxybuprocaine and proxymetacaine had a higher potency and provoked a shorter duration of sensory block compared with dopamine. The use of dopamine increased the quality and duration of skin antinociception caused by oxybuprocaine and proxymetacaine.